Low velocity impact analysis of pineapple leaf fiber (PALF) hybrid composites - Najeeb, Muhammad Imran; Hameed Sultan, Mohamed Thariq; Md Shah, Ain Umaira; Muhammad Amir, Siti Madiha; Safri, Syafiqah Nur Azrie; Jawaid, Mohammad; Shari, Mohamad Rabaie (MDPI AG, 2021)
The low-velocity impact behaviour of pineapple leaf fiber, PALF reinforce epoxy composite (P), PALF hybrid (GPG), and four-layer woven glass fiber (GGGG) composite was investigated. As for post-impact analysis, the damage evaluation was assessed through photographic images and X-ray computed tomography, using CT scan techniques. The key findings from this study are that a positive hybrid effect of PALF as a reinforcement was seen where the GPG shows the delayed time taken for damage initiation and propagation through the whole sample compared to GGGG. This clearly shows that the addition of fibers does have comparable composite properties with a fully synthetic composite. Through the visual inspection captured by photographic image, the presence of woven fiber glass mat in GPG presents a different damage mode compared to P. Moreover, CT scan results show extended internal damage at the cross-section of all impacted composite.